372. Comparing the Outcome of COVID-19 in Cancer and Non-Cancer Patients: an International Multicenter Study. (31st December 2020) - Hachem, Ray Y; Datoguia, Tarcila; Siddiqui, Bilal; Cruz, Ana Fernandez; Mori, Nobuyoshi; Fakhreddine, Suha; Lee, Dong-Gun; Gorak, Edward; Somer, Robert; Bhinder, Arvinder; Shelanski, Samuel; Dragivich, Tomislav; et al.
Abstract: Background: Our objective was to describe the clinical course, risk factors and outcomes of patients infected with COVID-19 around the globe comparing cancer to non-cancer patients. Methods: We conducted a retrospective cohort study of COVID-19 confirmed cases through an international multicenter collaboration including 17 centers around the world including the United States of America, Brazil, Europe, Far East, Middle East and Australia from January to date. We evaluated the patients' clinical characteristics, clinical course of the disease, hospitalization and outcome. Death was considered to be COVID-associated if it occurred within 30 days from the time of diagnosis. Results: Preliminary data on 571 patients included 186 cancer patients and 385 non-cancer patients. Cancer patients were more likely to have COPD and received steroids but were less likely to have COVID-related symptoms compared to non-cancer patients (84% vs 97%, p< 0.0001). The rate of pneumonia with hypoxia, non-invasive ventilation and mechanical ventilation were similar in both groups. Despite the fact that hospital admissions were significantly higher in non-cancer patients (70% vs 56%, p< 0.001), promising antiviral and immune-related therapy including remdesivir, convalescent plasma and immunomodulators were more commonly used in cancer patients compared to non-cancer patients (P=0.04). Cancer patients had a higher COVID-associated mortality rate compared to non-cancer patients (20% vs 11%, p=0.006). Conclusion: Despite the fact that cancer patients received more frequent antiviral and immune-related therapy, the mortality rate among cancer patients was significantly higher than non-cancer patients. Disclosures: Roy F. Chemaly, MD, MPH, FACP, FIDSA, Chimerix (Consultant, Research Grant or Support)Clinigen (Consultant)Merck (Consultant, Research Grant or Support)Novartis (Research Grant or Support)Oxford Immunotec (Consultant, Research Grant or Support)Shire/Takeda (Research Grant or Support)Viracor (Research Grant or Support) Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)